Role of adenoid hypertrophy in causation of chronic middle ear effusion - C. J., Timna; D., Chandrika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Abstract: Background: Hearing plays a valid role in speech development in children. Otitis media with effusion is one among the commonest causes of hearing loss in children especially below 12 years. It is defined as the presence of fluid in the middle ear without signs or symptoms of acute ear infection Methods: A prospective study was carried out in Lourdes Hospital, Kochi, over a period of 1 year from January 2013 to December 2013. Thirty patients with chronic middle ear effusion below the age of 12 years were selected for the study. Results: of the 30 patients 59.5% of patients were in the age group of 5-7 years of age, 16.6 % of patients were in the age group of 9-11 years of age .13.3% of patients each were in the age group of 3-5 years and 7-9 years of age.Among the 30 patients ,60% were male children and 40% patients were female children.Among the 30 patients , 40% of them had grade 3 adenoid hypertrophy ,33.3% of them had grade 2 adenoid hypertrophy and 30% of them had grade 4 adenoid hypertrophy and none had grade 1 adenoids. majority of them had grade 3 adenoid hypertrophy by endoscopic assessment.Among the 30 patients ,66.6 % of them had eustachian tube blockade by the adenoid mass and 33.4% of them didn’t have eustachian tube blockade. 100% of them with eustachian tube blockade found to have fluid on doing myringotomy and there was 20% of chance of absence of fluid ,if there is absence of eustachian tube blockade. Significant association was found between type B tympanogram and presence of fluid on myringotomy .92.5% of patients with type B tympanogram had fluid on myringotomy . 57.1 % of patients with type C tympanogram had fluid on doing myringotomy.There were 2 patients with grade 4 adenoid hypertrophy ,without eustachian tube blockade with bilateral type C tympanogram and there was bilateral dry tap on myringotomy. This reveals that type B tympanogram and eustachian tube blockade better predictor of otitis media with effusion than grade of adenoid hypertrophy. Conclusion: The present study showed that chronic middle ear effusion was found to be most common in the age group of 3-5 years of age group and relatively common in the male children. Tympanogram type B was found to be strongly associated with fluid on myringotomy .All the children with chronic middle ear effusion in the study group were found to have ,grade 3 grade 2,and grade 4 adenoid hypertrophy in the descending order of frequency.Grade 3 adenoid hypertrophy was present in majority of the children in the study group .Lateral adenoid hypertrophy ,abutting on the nasopharyngeal orifice of Eustachian tube was present in majority of children. Eustachian tube obstruction was found to be strongly associated with fluid on myringotomy and grommet insertion